The exhibition as an “urban thing” - Mark Dorrian; Adrian Hawker (Interstices, 2015)
This paper presents and discusses the design of a retrospective exhibition of the work of Metis, shown at the Arkitektskolen, Aarhus, Denmark between 10 October and 14 November 2014 and at Edinburgh College of Art between 27 March and 6 April 2015. Making reference to Bruno Latour's distinction between 'objects' and 'things', as developed in his influential article 'Why has critique run out of steam?' (2004), it speculates on what it would mean to conceptualise an exhibition as a 'thing' – that is, as a gathering of relations – and how this might affect our approach to it. In the case of the Metis exhibition, which was titled 'On the Surface', this issue is related to the agency of the large-scale textile drawing that covered the floor of the gallery, forming a kind of raft within it upon which visitors walked. Acting as a gathering space for both exhibits and visitors, the drawing was constituted through a complex of representational modalities, which put the seven exhibited projects into play with one another in such a way as to resist their stabilisation and resolution into a sequence of objects.